2010
DOI: 10.1111/j.1542-4758.2010.00478.x
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term effects of arteriovenous fistula creation on the development of pulmonary hypertension in hemodialysis patients

Abstract: The aim of this prospective study was to evaluate long-term effects of arteriovenous fistula (AVF) on the development of pulmonary arterial hypertension (PAH) and the relationship between blood flow rate of AVF and pulmonary artery pressure (PAP) in the patients with end-stage renal disease (ESRD). This prospective study was performed in 20 patients with ESRD. Before an AVF was surgically created for hemodialysis, the patients were evaluated by echocardiography. Then, an AVF was surgically created in all patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 16 publications
2
42
2
Order By: Relevance
“…11 With regard to pulmonary blood flow, several studies focused on the role of AVF and its consequent increased cardiac output. Although not confirmed by our results and some other studies, 6,19 current evidence is in favor of a role of AVF presence, duration, and blood flow in the pathogenesis of PAH in patients on dialysis. 3,11,20,21 Another factor that can contribute to the development of PAH by increasing cardiac output is anemia, 5,7,10,18 which was confirmed by our univariate but not multivariate analyses probably due to the small sample size.…”
Section: Underlying Mechanisms For Pahcontrasting
confidence: 56%
“…11 With regard to pulmonary blood flow, several studies focused on the role of AVF and its consequent increased cardiac output. Although not confirmed by our results and some other studies, 6,19 current evidence is in favor of a role of AVF presence, duration, and blood flow in the pathogenesis of PAH in patients on dialysis. 3,11,20,21 Another factor that can contribute to the development of PAH by increasing cardiac output is anemia, 5,7,10,18 which was confirmed by our univariate but not multivariate analyses probably due to the small sample size.…”
Section: Underlying Mechanisms For Pahcontrasting
confidence: 56%
“…It was reported that compression of AVF can decrease cardiac output and sPAP, and that an AVF increases sPAP via elevation of cardiac output (23). In the present study the prevalence of PHT in stage 5 CKD patients with and without an AVF was similar (53.3% vs. 58.3%, respectively) and, as previously reported, there wasn't an association between the presence of an AVF and PHT (24,25). Anemia can also contribute to the development of PHT by increasing cardiac output and exacerbating hypoxia (26).…”
Section: Discussionsupporting
confidence: 75%
“…Impaired Caphosphorus balance and secondary hyperparathyroidism play an important role in the pathogenesis of vascular calcification (29). Although researches has shown that there isn't an association between pulmonary calcification and the PTH level (30,31), it was also reported that in dogs with experimentally induced CKD (25,27) reported that there wasn't a significant difference in PTH between CKD patients with and without PHT. They also reported that there wasn't a correlation between the Ca level and PHT.…”
Section: Discussionmentioning
confidence: 99%
“…In patients established on RRT, PH has been reported to be more prevalent affecting 30-58% of patients receiving HD [2,4,10,11] with the largest and most recent study reporting a prevalence of 38% [12]. In patients receiving peritoneal dialysis (PD) the reported prevalence varies between 12.5 and 42% [13].…”
Section: Epidemiologymentioning
confidence: 99%